Anesthetic management for laparoscopy surgery in a patient with residual coarctation of aorta and mild aortic stenosis - Renu Sinha; Rakesh Garg (Wolters Kluwer Medknow Publications, 2011)
Perioperative management of patients with congenital heart disease is a challenge for the anesthesiologist. We present successful anesthetic management for diagnostic laparoscopy and cystectomy for tubo-ovarian mass in a case of residual coarctation of the aorta along with bicuspid aortic valve and mild aortic stenosis.